Bakti TNI Operation as Implementation of State Defense Strategic Vision Mission - Selfira Salsabilla; Aris Sarjito (International Journal of Social Science and Business, 2021)
Indonesia implements a total defense system where this system involves all components of the nation, which in its implementation is carried out according to their respective capabilities and capacities. one manifestation of the universal defense system is the existence of TNI Operational Service activities. As the implementation of the strategic vision, it is one of the regional development activities to create space, equipment, and harsh combat conditions to ward off threats, challenges, obstacles, and disturbances that may arise in the current strategic environmental conditions. This study aims to analyze the vision and mission of national defense and how the National Defense Strategy Policy in the Framework of Creating Tough Space, Tools and Conditions (RAK Juang) to Support National Defense. This type of research is a literature study approach where the data sources used are journals, articles, books, and other relevant sources. The results of the research are that the achievement of goals in the national defense policy, namely creating a vital fighting space, tools and conditions to support national defense, can be realized through TNI Service Operations activities which are carried out in stages, gradually and integrated with local government development programs so that they can reflect the unity of the TNI. The implementation of military operations to create a formidable battle space with physical activities has contributed to the interests of development in the context of prosperity.